Regulation of Osteoclastogenesis and Bone Resorption by miRNAs - Inoue, Kazuki; Ng, Courtney; Xia, Yuhan; Zhao, Baohong (Frontiers in Cell and Developmental Biology, 2021)
Osteoclasts are the sole specialized bone-resorbing cells that contribute to physiological bone development and remodeling in bone metabolism throughout life. Abnormal generation and activation of osteoclasts lead to excessive bone resorption in pathological conditions, such as in osteoporosis and in arthritic diseases with bone destruction. Recent epigenetic studies have shed novel insight into the dogma of the regulation of gene expression. microRNAs belong to a category of epigenetic regulators, which post-transcriptionally downregulate the expression of target genes and thereby control a variety of biological events. In this review, we discuss miRNA biogenesis, the mechanisms utilized by miRNAs, a few miRNAs that play important roles in osteoclast differentiation, fusion, resorbing activity, survival, and osteoblast-to-osteoclast communication, and their translational potential and challenges in bone biology and skeletal diseases.